Social media data mining and analytics - Szabó, Gábor (John Wiley & Sons, 2019)
Social media is a rich source of big data, so much so that 90% of Fortune 500 companies are investing in big data initiatives to help them predict consumer behavior. Knowing the most effective ways to mine social media data can help you acquire information that generates amazing business results. Social media is unstructured, dynamic, and future-oriented. Effective, insightful data mining requires new analytical tools and techniques. Written by experts at social networking companies, Social Media Data Mining and Analytics provides a hands-on course that teaches you how to use state-of-the-art tools and sophisticated data mining techniques specifically geared to social media. It digs deeply into the mechanics of collecting and applying social media data to understand customers, define trends, and make predictions that can improve analytics for growth and sales.